Industry Matters: The Impact of Business Nature on Tax Avoidance and Financial Fraud Dynamics - Maulina Dyah Permatasari; Nizar Febriana (Jurnal Akuntansi Bisnis Pelita Bangsa, 2025)
This study investigates the effect of tax avoidance (TA) on financial statement fraud (FD) and examines the moderating role of the nature of industry (NI) among publicly listed companies in Indonesia from 2021 to 2024. Using a sample of 150 firm-year observations from manufacturing and service sectors, the analysis employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and moderated relationships. The results reveal that TA has a positive and significant influence on FD, suggesting that aggressive tax strategies increase the likelihood of fraudulent financial reporting. Furthermore, NI significantly moderates this relationship, with higher industry complexity and discretion strengthening the TA–FD link. These findings support agency theory and the fraud triangle framework, indicating that managerial opportunism, facilitated by industry characteristics, can escalate fraudulent behaviors. This study provides important implications for regulators, auditors, and policymakers to incorporate both firm-specific and industry-level risk indicators in fraud prevention strategies.